Preliminary testing for utilising oil palm empty fruit bunch fibre in home compost making and its usability in planting medium towards growth of bird’s-eye chili (Capsicum annum) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
In this preliminary study, a home-based composting routine utilising waste oil palm empty fruit bunch (OPEFB) fibre, garden and kitchen waste, and home-made effective microorganism (EM) solution was carried out. The purpose of this research was to explore potential waste utilisation practice which can start from home. The 9 compost premix samples prepared with different amounts (7%, 14%, 50%, 100%) of OPEFB fibre displayed varying durations of composting time from 4 to 8 weeks. It was observed that compost containing higher amounts of OPEFB fibre took a longer time to mature. The addition of the EM solution to the compost premix samples aided the decomposition of the OPEFB fibre. The compost sample made of 100% OPEFB fibre took 8 weeks of composting period while its replicate sample which was treated with EM took 7 weeks to compost. The usableness of the home-made compost in a planting medium consisting of soil, compost and cocopeat with a ratio of 3:1:1 was tested to grow bird’s-eye chili seeds. Based on the results, soil treated with compost containing OPEFB fibres showed better results for plant growth compared to soil having no compost and with control compost sample (0% OPEFB fibre). It was also observed that compost treated with EM containing 14% OPEFB fibre and 86% vegetable scraps with an initial C: N ratio of 29.9:1 showed the best result towards the plants growth. Based on this finding, home-made compost utilising OPEFB fibre can be included as part of planting medium to support plant growth.
Keywords: aerobic composting; cocopeat; composting; effective microorganisms; OPEFB fibre